PHYSICAL QUALITY OF BROILER MEAT WITH PROVISION OF AMINO LYSINE AND METHIONENE THROUGH DRINKING WATER IN CLOSED HOUSE CAGE - I M. D. A, Pratama; Astawa, I P. A.; Suasta, I M. (Jurnal Peternakan Tropika, 2021)
This study aims to determine the physical quality of broiler chicken meat given the amino acids lysine and methionine through drinking water in a cage near the house. This study used a completely randomized design (CRD) consisting of 4 treatments, namely: treatment A control (broiler chickens without the amino acids lysine and methionine), B (administration of amino acids lysine and methionine as much as 0.02%), C (administration of amino acids lysine and methionine as much as 0.025%), D (administration of amino acids lysine and methionine as much as 0.03%). Each treatment had 4 replications and each replication used 12 broiler chickens. The variables observed were meat pH, water holding capacity, raw and cooked losses. The data were analyzed using a variance fingerprint. The results of the study showed that the pH of broiler meat given the amino acids lysine and methionine at a level of 0.025% showed significantly different results (P<0.05) Based on the results of the study, it can be concluded that that the administration of amino acids lysine and methionine at levels of 0.025% through drinking water had a significant effect on the pH value of meat and had no significant effect on water holding capacity, raw and cooked losses. Keywords : broiler meat, physical quality, dringking, waterlysine and methionine